Properties of solid hydrogen doped by heavy atomic and molecular impurities: Low-Temperature Thermodynamics and Structure - Galtsov, N.N.; Prokhvatilov, A.I.; Shcherbakov, G.N.; Strzhemechny, M.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Using powder x-ray diffraction we studied the structural characteristics of normal and para hydrogen crystals doped with Ar, Kr, N2, and O2 impurities over the range from 5 K to the melting point of the hydrogen matrix. It has been established that in spite of very low solubility of the dopants in solid hydrogen, these impurities appreciably affect the structural characteristics. Inparticular, only nitrogen impurities do not change the molar volume of the matrix, the other three make the matrix expand. The Ar and Kr impurities also change the c/a ratio of the hcp matrix. The fact that both Ar and O2 have smaller molar volumes than hydrogen may be treated as evidence that these impurities form van der Waals complexes with the hydrogen lattice environment.